Efektivitas Model Quantum Learning Pada Pembelajaran PAI Di Smp Al-Azhar Menganti Gresik - Rohmatul Badi'ah (Jurnal Pendidikan Agama Islam Miazhar, 2021)
The delivery of PAI subject matter, especially Friday prayer material, needs to be designed an appropriate learning strategy because many students are confused about the difference between the terms, pillars and sunnah of Friday prayers, namely students will get new experiences in learning, besides that students will feel comfortable . PAI learning strategies must be designed in such a way by considering the progress of science and technology in addition to relying on sensory experience towards the formation of logical conclusion experiences. By applying Quantum Learning, it is possible to achieve fun learning for students and improve the quality of PAI learning in secondary education. In addition, it can also improve the application of the current curriculum and increase understanding and create a conducive learning atmosphere. The problem that can be formulated is how effective is Quantum Learning in PAI learning at SMP Al-Azhar Menganti Gresik? To find out the effectiveness of Quantum Learning in PAI learning at SMP Al-Azhar Menganti Gresik in depth. The method used in this research is quasi-experimental. According to Sudjana, quasi-experimental is an experimental study whose control is adjusted to the existing conditions (situational). The process required in the overall planning and implementation of research is research design. The research design used in this study was a random pretest posttest design. Techniques in collecting the data needed are observation, questionnaires, and learning outcomes questionnaires. The data analysis technique used is product moment correlation.